Analyzing Failure Risks in Clean Water Distribution Networks Using the Failure Mode and Effect Analysis (FMEA) - Shalihin, Ahmad; Sari, Dea Kemala; Nasution, Harmein (Airlangga Journal of Innovation Management, 2025)
Reliable provision of clean water is is a major challenge in managing public infrastructure, particularly in areas with rapid population growth and complex geography. One of the clean water service unit in Padang Sidempuan City faces obstacles in water transmission and distribution, including pipe damage due to aging infrastructure, non-standard materials, ineffective gravity-based systems, and limited raw water sources. This study aims to identify and analyze these inhibiting factors using the Failure Mode and Effects Analysis (FMEA) method. Data were collected through field observations, interviews with technical personnel, and review of operational documents, then analyzed by calculating the Risk Priority Number (RPN) to determine repair priorities. The findings reveal the highest RPN of 720, in areas with elevation issues, where gravity flow fails to maintain sufficient pressure posing the greatest operational risk. The second most critical issue involves failure of water flow due to elevation and inadequate pressurization, with an RPN of 630, highlighting the gravity system’s limitations. Pipe damage, mainly from high internal pressure and poor maintenance, scored an RPN of 560, marking it as another high-priority issue. Based on these findings, this study recommends upgrading the system by installing mechanical pressure devices (booster pumps), replacing pipes with standard-compliant materials, and exploring alternative water sources These improvements are essential for reducing system vulnerability and improving service reliability. The results underscore that applying FMEA systematically is a practical approach for prioritizing technical interventions and enhancing the overall performance of regional clean water supply systems.